In vivo exposure of the marine sponge Chondrilla nucula Schmidt, 1862 to cadmium (Cd), copper (Cu) and lead (Pb) and its potential use for bioremediation purposes. (February 2018) - Ferrante, Margherita; Vassallo, Marilisa; Mazzola, Antonio; Brundo, Maria Violetta; Pecoraro, Roberta; Grasso, Alfina; Copat, Chiara
Abstract: The study aimed to test the cadmium (Cd), copper (Cu) and lead (Pb) bioaccumulation capacity of the marine sponge Chondrilla nucula and to measure the expression of metallothioneins (MTs) by a western blotting assay to explore metal tolerance and its potential use as a bioremediator in contaminated coastal areas. C. nucula was sampled in a protected marine area in order to perform experiments on organisms living in a healthy environment. Under laboratory conditions, the sponges were exposed to increasing concentrations of Cd, Cu and Pb in tanks filled with artificial seawater set up for the experiments. For each metal, three waterborne concentrations (mgL −1 ) of Cd (0.02–0.04-0.08), Cu (0.1–0.2-0.4) and Pb (0.2–0.4-0.8) were considered separately. SPSS 20.0 was used for statistical analysis. Significant differences in bioaccumulation across levels of each metal were highlighted. Moreover, the amount accumulated in sponges increased proportionately with increasing levels of exposure for each metal as well as MT expression after Cd and Pb exposure. The results demonstrate the efficiency of C. nucula in accumulating high levels of Cu, but a low tolerance to progressively higher concentrations for Cd and Pb. The study suggests the suitability of the use of this species in bioremediation plans for moderately contaminated environments. However, the biological response in the field should be verified by the use of transplanted organisms from a control site to a polluted site. Highlights: Cd, Pb and Cu bioaccumulation capacity of the marine sponge Chondrilla nucula was evaluated in vivo. The expression of metallothioneins (MTs) was measured to explore metal tolerance. The results demonstrate the efficiency of C. nucula in accumulating metals in proportion to the pollution level. The species can be used in programs of environmental remediation for moderate contaminated site. In highly Cd and Pb contaminated environments, the species has a low tolerance.